Frequency and dc bias voltage dependent dielectric properties and electrical conductivity of BaTiO3SrTiO3/(SiO2)x nanocomposites. Issue 9 (15th June 2019) - Slimani, Y.; Unal, B.; Hannachi, E.; Selmi, A.; Almessiere, M.A.; Nawaz, M.; Baykal, A.; Ercan, I.; Yildiz, M.
Abstract: BaTiO3 SrTiO3 /(SiO2 )x nanocomposites (x = 0, 0.5, 1, 2 and 5%) were produced through solid state reaction. The morphological, structural, spectral, and optical properties were investigated by scanning electron microscope, X-ray powder diffraction (XRD), Fourier transform-infrared spectroscopy and ultraviolet–visible diffuse reflectance spectrophotometry, respectively. All XRD patterns illustrate two distinct phases of BaTiO3 and SrTiO3 with cubic structure. No impurity was noticed for x ≤ 0.5% nanocomposite. However, Ba2 TiSi2 O8 secondary phase starts to appear for x ≥ 1%. Electrical and dielectric properties were used to analyze the dielectric constant and loss, the conductivity as well as dissipation factors as functions of both frequencies and dc bias voltage for BaTiO3 SrTiO3 /(SiO2 )x nanocomposites. In general, conductivity and dielectric loss obey power law tendencies against frequencies. However, the dc bias was found to be less effective to conduction mechanism having a slight change for a variety of SiO2 percentages.